Assessing the germination response of selected species to lavender hydrolate - Ugrinov, Stefan; Mandić, Nataša; Popov, Milena; Aćimović, Milica; Stojanović, Tijana; Rodić, Anastasia (Acta herbologica, 2026)
The present study investigates the effect of lavender hydrolate on the germination of selected cultivated and weed species. Lavender hydrolate, known for its diverse biological activities, is a byproduct of the lavender essential oil distillation process. The study examined the effects of four different lavender hydrolate concentrations (10, 20, 50, and 100%) on the germination of sunflower (Helianthus annuus), wheat (Triticum sp.), lambsquarters (Chenopodium album), and purslane (Portulaca oleracea). The findings indicate that lavender hydrolate significantly reduced the seed germination of C. album, with the germination rates being 37.25-50.98% in the case of lower concentrations. The most pronounced effects were observed for P. oleracea, in which all the concentrations significantly impaired the germination. Notably, by applying the 10, 20, 50, and 100% hydrolate solution, the germination was reduced by 78, 92, 88, and 100%, respectively. The results revealed that lavender hydrolate had a significant inhibitory effect on the germination of all the tested species, with the highest concentration showing the strongest inhibition. Statistically significant differences in the growth of the hypocotyl and epicotyl of the weed plants were observed for all the tested concentrations compared to the control. The hydrolate more effectively reduced the growth rates of the weeds than of the cultivated crops, indicating its potential as a bioherbicide, particularly at higher concentrations.
Keywords: bioherbicides, weed control, Chenopodium album, Portulaca oleracea